THE EFFECT OF 50% EDAMAME BEAN (GLYCINE MAX L. MERRIL) EXTRACTS ON THE SURFACE ROUGHNESS OF HEAT-CURED ACRYLIC RESIN - Lusi Hidayati; Yohana Maria Penga; Leliana Sandra Devi; Ayudia Yohanna Widya Kusumastuti (Journal of Vocational Health Studies, 2025)
Background: Edamame bean (Glycine max L. Merril) extract is an alternative to denture cleanser because it contains antifungal and antibacterial compounds, such as flavonoids. However, flavonoids may increase the surface roughness of heat-cured acrylic resin. Purpose: This research aims to analyze the effect of 50% edamame bean extract as a denture cleanser on the surface roughness of heat-cured acrylic resin. Method: Twenty four square shaped heat-cured acrylic resin plates of 10 x 10 x 2 mm were divided into four groups: A1, A2, B1, and B2. Each group was immersed in distilled water (A1 for four days and A2 for 11 days) and 50% edamame bean extract (B1 for four days and B2 for 11 days). The surface roughness was measured using a surface roughness tester TR 220. The data were then analyzed using the Two Way ANOVA test followed by the Tukey HSD test with a significance value of p-value < 0.05. Result: The average surface roughness in heat-cured acrylic resin increased in 50% edamame extract immersion for four and 11 days. The highest increase was experienced in 50 % edamame extract immersion for 11 days with a value of 0.158 μm. In contrast, the distilled water immersion group noted the lowest surface roughness for four days and 11 days. Conclusion: Edamame extract significantly affects the surface roughness of heat-cured acrylic resin after immersion for four and 11 days.